Pengaruh Financial Distress, Auditor Switching, dan Audit Report Lag terhadap Opini Audit Going Concern (Studi Empiris Pada Perusahaan yang Tergabung dalam Jakarta Islamic Index 70 Periode 2018-2022) - Putra, Randika; Annisa, Dea (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This research aims to examine Financial Distress, Auditor Switching, and Audit Report Lag on Going Concern Audit Opinions in Companies that are Members of the Jakarta Islamic Index 70 for the 2018-2022 Period. This research uses a quantitative approach and uses associative methods. The type of data used in this research is secondary data. The data analysis method used in this research is Logistic Regression Analysis using the Eviews version 10 application and Microsoft Excel. The population used in this research is companies that are members of the Jakarta Islamic Index 70 for the 2018-2022 period. The data collection technique in this research is a purposive sampling technique with the results of 70 research populations becoming 37 research samples processed in this research. The research results show that simultaneously financial distress, auditor switching, and audit report lag influence going concern audit opinion. Partially, financial distress has an effect on going concern audit opinion, while auditor switching and audit report lag have no effect on going concern audit opinion.